Pengaruh Perlakuan Pemberian Air Irigasi pada Budidaya SRI, PTT dan Konvensional terhadap Produktivitas Air - Subari Subari; Marasi Deon Joubert; Hanhan Ahmad Sofiyuddin; Joko Triyono (Jurnal Irigasi, 2012)
The limitedness water availability and increased water needs can cause a conflict of interest in water allocation. Thus, efforts to save water usage needs to be done, especially for rice cultivation that requires a lot of water. Therefore, alternative irrigation and rice cultivation technology which can save water need to be investigated. Water savings in practice can be done by changing the pattern of irrigation in the field without reducing the production, i.e. by reducing the amount of water for the land preparation period and plant growth period. The study was conducted to determine the water productivity of different irrigation and paddy cultivation method (i.e. the SRI method, ICM and conventional) in the from of research demonstration plot. This paper presents the results of these studies, especially regarding water productivity in each irrigation and paddy cultivation method. The results showed irrigation water requirement during land preparation on SRI 22-47 mm; ICM 24-47 mm and conventional 30-68 mm. During the growth period, water consumption in the conventional cultivation is the highest with a mean of 577 mm. Other cultivation treatments showed lower results, i.e. SRI 324 mm and ICM 544 mm, and water productivity for SRI=1,9 Kg/m3; ICM=1,1Kg/m3 and for conventional = 1,0Kg/m3.